Falling-film thermosyphons: Application to water harvesting from humid gas streams. (January 2021) - Zhong, W.; He, T.; Butcher, Tom; Trojanowski, Rebecca; Mamalis, Sotirios; Wagner, Tim; Chudnovsky, Yaroslav; Worek, William; Wang, Ya; Longtin, Jon P.
Highlights: The falling-film thermosyphon (FFTS) is introduced and preferred for large-scale applications. Several traditional thermosyphon (TTS) limits are eliminated, resulting in higher maximum heat fluxes for the same physical evaporator size for FFTS. A temperature boundary condition for the evaporator is introduced and the simulation model is built. The model is compared with FFTS experiments to condense water from a moist air stream with good agreement found. Abstract: Water harvesting from humid gas streams is central to fresh-water production, desalination, and particulate removal from combustion gas streams. Two-phase thermosyphons are well suited for these applications due to their very low thermal resistance, but have several operating limits at the high heat flows required for such applications. This work introduces the falling-film thermosyphon for large-scale condensation applications. Working fluid is pumped to the top of the evaporator to provide the evaporating liquid film on the inner tube wall, rather than by vapor condensation. The flooding, dry-out and pool-boiling limits are eliminated, resulting in significantly higher maximum heat fluxes for the same physical evaporator size. Additionally, the condenser no longer needs to be located vertically above the evaporator, which allows for a standard steam condenser to be used. A model for the condensation process in humid air was developed that estimates the fluid and heat transfer and is confirmed experimentally. Other benefits include the use of a high-thermal-conductivity polymer material for the evaporator section to minimize corrosion, and the ability to impose a temperature boundary condition on the evaporator, which is made possible due to the elimination of a liquid pool.